DEVELOPMENT OF POLYELECTROLYTE BASED BIOCONJUGATES USING WITH SYNTHETIC VIRAL PEPTIDES - Ozdemir, Zafer Omer; Akdeste, Zeynep (YILDIZ TECHNICAL UNIV, 2011)
Bioconjugates can be synthesized by reaction of synthetic peptides and polyelectrolytes. They are biologicallay important molecules. Their application on biology and nanotechnology fields has great potential. There are lots of researchs related to functional biopolymer systems in last years. These researchs are about synthesis, characterization and application properties of biologically important polyelectrolytes. This work is aimed to giving information about polyelectrolytes, bioconjugation, microwave energy, solid phase peptide synthesis
Keywords: Bioconjugation; microwave; polyelectrolyte; solid phase peptide synthesis; BIODEGRADABLE POLYMERS; POLYETHYLENE-GLYCOL; MICROWAVE-OVENS; MICROCAPSULES; ENDOCYTOSIS; SUBSTANCES; DEPOSITION; PROTEINS; RELEASE; Engineering